ANALISIS THE SEVEN PILLARS OF INFORMATION LITERACY PADA KEMAMPUAN LITERASI INFORMASI MAHASISWA PROGRAM STUDI ILMU KOMUNIKASI UNIVERSITAS ISLAM NUSANTARA TERHADAP PENULISAN BERITA - Nur Ilahi, Tarlina; Yanti, Dama; Nurrohmah, Oom (Jurnal Perpustakaan dan Informasi, 2025)
The phenomenon of society 5.0 causes a flood of information on a very large scale, making it important to apply information literacy skills. Information literacy can help in sorting, identifying and evaluating information so that the information obtained is relevant, especially in the tertiary sector, students are encouraged to be wise in sorting information from trusted sources, especially students with a concentration in Journalism in the Communication Science Study Program at Nusantara Islamic University. The aim of this research is to analyze information literacy skills using the seven pillars literacy model in Communication Science Study Program students at Islamic Nusantara University in writing news. This research uses descriptive qualitative research methods. Data obtained from interviews and documentation studies with data reduction analysis, data presentation and drawing conclusions. The research results of students from the Communication Science Study Program at Islamic Nusantara University were able to analyze news writing with their information literacy skills, but there are several aspects that need to be improved, one of which is information management, expanding knowledge related to the visual elements of news and collaborating with news practitioners. Keywords: Information Literacy, Seven Pillars Literacy Model, Students